Kirk-Othmer Encyclopedia of Chemical Technology 2000
DOI: 10.1002/0471238961.1315122519200905.a01
|View full text |Cite
|
Sign up to set email alerts
|

Molybdenum Compounds

Abstract: Molybdenum, found naturally as molybdenite, is converted through MoO 3 to compounds in a wide range of oxidation states, coordination numbers, and states of aggregation. The diverse chemistry of molybdenum is manifest in a wide array of uses in biological and industrial systems. Molybdenum, an essential component of many enzymes, plays a primary role in nitrogen fixation and nitrate reduction in bacteria and plants, and sulfite and xanthine oxidation for microorganisms, plants, and anim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 58 publications
0
4
0
Order By: Relevance
“…The chemistry of transition metal sulfur systems has attracted increasing attention due to their industrial and biological relevance . The industrial interest of transition metal sulfur species includes catalysis, corrosion, lubrication, battery technology, , etc. In many biological systems, it has been found that sulfur coordination is necessary for the functioning of numerous biological transition metal centers as a key part of its active site. , Nowadays, many transition metal sulfides have been utilized as enzymes and heterogeneous catalysts, where transition metal centers play an important role as potentially reactive sites and are capable of reacting with a large number of small molecules such as H 2 , C 2 H 6 , H 2 O, O 2 , SO 2 , and OCS.…”
Section: Introductionmentioning
confidence: 99%
“…The chemistry of transition metal sulfur systems has attracted increasing attention due to their industrial and biological relevance . The industrial interest of transition metal sulfur species includes catalysis, corrosion, lubrication, battery technology, , etc. In many biological systems, it has been found that sulfur coordination is necessary for the functioning of numerous biological transition metal centers as a key part of its active site. , Nowadays, many transition metal sulfides have been utilized as enzymes and heterogeneous catalysts, where transition metal centers play an important role as potentially reactive sites and are capable of reacting with a large number of small molecules such as H 2 , C 2 H 6 , H 2 O, O 2 , SO 2 , and OCS.…”
Section: Introductionmentioning
confidence: 99%
“…Co(NO3)2 is produced by reacting CoO with nitric acid (Richardson, 2000), and the energy and material flow data for production of both CoO and nitric acid are available in GREET. Ammonium heptamolybdate is obtained by reacting ammonia solution with MoO3, while MoO3 is produced by calcining MoS2 ore (Stiefel, 2000). We describe the production of ammonium heptamolybdate also known as ammonium molybdate in a separate report (Benavides et al 2015).…”
Section: Alcohol Synthesis Catalystmentioning
confidence: 99%
“…Co(NO 3 ) 2 is produced by reacting CoO with nitric acid (Richardson, 2000), and the energy and material flow data for production of both CoO and nitric acid are available in GREET. Ammonium heptamolybdate is obtained by reacting ammonia solution with MoO 3 , while MoO 3 is produced by calcining MoS 2 ore (Stiefel, 2000). GREET does not include data specific to molybdenum compounds.…”
Section: Alcohol Synthesis Catalystmentioning
confidence: 99%